Pengaruh solarisasi tanah dan pemberian dosis Trichoderma harzianum dalam pengendalian penyakit layu fusarium pada cabai (Capsicum annum L.) - Varida Risma Wati; Yafizham Yafizham; Eny Fuskhah (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2020)
ABSTRACT This research was conducted to determine the effectiveness of the application of soil solarization and the dosage of Trichoderma harzianum in controlling fusarium wilt. This research was arranged using factorial CRD 2 x 4 treatments and 4 replications. The first factor is soil solarization treatment consisting of S0 = without solarization and S1 = solarization for 4 weeks, the second factor is dose of Trichoderma harzianum which consists of A0 = 0 g / l, A1 = 25 g / l, A2 = 50 g / l and A3 = 75 g / l. Data were analysed using descriptive statistic and analysis of variance (ANOVA) and if there was significant it was followed by DMRT (α = 5%). The results showed that solarization can increase soil temperature by 20.98% or 8.5oC, and there was an interaction between solarization and the dose of Trichoderma harzianum to reduce the percentage of disease incidence and disease intensity of fusarium wilt. Addition of doses Trichoderma harzianum 50 g / l can increase chili production by 63.56%. Soil solarization and dose of T. harzianum 50 g / l are effective in controlling fusarium wilt and able to increase chili production.Keywords : Fusarium oxysporum, soil solarization, Trichoderma harzianum, chili. ABSTRAK Tujuan dari penelitian ini adalah untuk mengetahui keefektifan penerapan solarisasi tanah dan dosis Trichoderma harzianum dalam mengendalikan penyakit layu fusarium. Penelitian ini disusun menggunakan RAL faktorial 2 x 4 perlakuan dan 4 ulangan. Faktor pertama adalah perlakuan solarisasi tanah yang terdiri dari S0 = Tanpa solarisasi dan S1 = Solarisasi selama 4 minggu, faktor kedua adalah dosis Trichoderma harzianum yang terdiri dari A0 = 0 g/l, A2 = 25 g/l, A3 = 50 g/l dan A4 = 75 g/l. Analisis data penelitian dilakukan secara deskriptif dan analisis ragam (ANOVA), apabila berpengaruh nyata dilanjutkan dengan uji DMRT taraf α =5%. Hasil penelitian menunjukkan bahwa solarisasi dapat meningkatkan suhu tanah sebesar 20,98% atau 8,5oC, dan terdapat interaksi antara solarisasi dengan dosis T. harzianum terhadap penurunan persentase kejadian penyakit dan intensitas serangan penyakit layu fusarium. Penambahan dosis Trichoderma harzianum 50 g/l sudah dapat meningkatkan produksi cabai sebesar 63,56%. Solarisasi tanah dan dosis T. harzianum 50 g/l efektif dalam mengendalikan penyakit layu fusarium dan meningkatkan produksi cabai.Kata kunci : Fusarium oxysporum, solarisasi tanah, Trichoderma harzianum, cabai.